Mental Health Functioning in the Human Rights Field: Findings from an International Internet-Based Survey. - Amy Joscelyne; Sarah Knuckey; Margaret L Satterthwaite; Richard A Bryant; Meng Li; Meng Qian; Adam D Brown (PLoS ONE)
Human rights advocates play a critical role in promoting respect for human rights world-wide, and engage in a broad range of strategies, including documentation of rights violations, monitoring, press work and report-writing, advocacy, and litigation. However, little is known about the impact of human rights work on the mental health of human rights advocates. This study examined the mental health profile of human rights advocates and risk factors associated with their psychological functioning. 346 individuals currently or previously working in the field of human rights completed an internet-based survey regarding trauma exposure, depression, posttraumatic stress disorder (PTSD), resilience and occupational burnout. PTSD was measured with the Posttraumatic Stress Disorder Checklist-Civilian Version (PCL-C) and depression was measured with the Patient History Questionnaire-9 (PHQ-9). These findings revealed that among human rights advocates that completed the survey, 19.4% met criteria for PTSD, 18.8% met criteria for subthreshold PTSD, and 14.7% met criteria for depression. Multiple linear regressions revealed that after controlling for symptoms of depression, PTSD symptom severity was predicted by human rights-related trauma exposure, perfectionism and negative self-appraisals about human rights work. In addition, after controlling for symptoms of PTSD, depressive symptoms were predicted by perfectionism and lower levels of self-efficacy. Survey responses also suggested high levels of resilience: 43% of responders reported minimal symptoms of PTSD. Although survey responses suggest that many human rights workers are resilient, they also suggest that human rights work is associated with elevated rates of PTSD and depression. The field of human rights would benefit from further empirical research, as well as additional education and training programs in the workplace about enhancing resilience in the context of human rights work.